Al-Maqrizi’s Thought on Theory of Quantity of Money: A Historical Perspective - Setiawan Bin Lahuri; Khoirul Umam; Chindy Chintya Cahya (UIN Sunan Gunung Djati Bandung, 2022)
Historically, the theory of quantity of money was first proposed by Irving Fisher who was one of the famous scientists of the classical period (1867-1947). The existence of the theory of quantity of money put forward by Irving Fisher made the public both practitioners and academics forget that long before Irving Fisher proposed the theory Al-Maqrizi as a Muslim scholar had initiated the quantity of money. The purpose of this study was to reveal and prove that in the field of economics Al-Maqrizi as a Muslim scholar had first initiated the quantity of money compared to Irving Fisher as a Western scientist. The methodology used in this study is qualitatively descriptive, namely by collecting documentation both from previous research and existing data then researchers analyze and explain descriptively. The results of this study state that Al-Maqrizi's thought of the concept of quantity of money at that time was more detailed and detailed than the theory of the quantity of money put forward by Irving Fisher. It's just that at that time the idea was not yet known as the quantity of money theory as it is known at this time.Keywords: Quantity of Money, Maqrizi’s thought, Muslim scholar